The Influence of Plasma Nitriding Technology Parameters on the Hardness of 18XГT Steel Parts - Van, Nguyen Thai; Ky, Le Hong (Engineering, Technology & Applied Science Research, 2024)
This article presents the results of the research on the influence of plasma nitriding technology parameters on the working surface hardness of machine parts made of previously hardened 18XГT steel. A total of 27 experiments were conducted on the H4580 Eltrolab instrument. Minitab software was used to process the experimental results. The regression function set up with visual charts was utilized as the basis for analysis of the influence of temperature, time, and gas permeation concentration on the working surface hardness. Analysis of variance (ANOVA) showed that all the nitriding technology parameters influenced the regression function. The permeation temperature TL had the greatest influence on hardness, while the permeation time h and the gas permeation concentration G1 had less influence. When the double interaction between the parameters was considered, it was shown that these pairs also had a large influence on the surface hardness, but at different levels.